Origin of negative Δ33S anomalies and Δ36S–Δ33S trends in 3700 Ma Isua sulfides: Searching for evidence of Eoarchean life in dolomitic meta-sedimentary rocks - Janaína N. Ávila; Allen P. Nutman; Vickie C. Bennett; Clark R.L. Friend; Martin Van Kranendonk (Precambrian Research, 2026)

Zircon geochronology of the Gordonbrook Serpentinite: A fragment of mantle wedge within the New England Orogen, eastern Australia - George G.F. Murray; Solomon Buckman; Allen P. Nutman; Wanchese M. Saktura; Jonathan C. Aitchison; Vickie C. Bennett; Zhen Yan; Changlei Fu (Lithos, 2026)

Prenatal exposure to organophosphate ester flame retardants and plasticizers and maternal immune responses in three ECHO cohorts - Jiwon Oh; Judy Van de Water; Thomas G. O'Connor; Kristin Scheible; Anne P. Starling; Dana M. Dabelea; Raina N. Fichorova; Rebecca J. Schmidt; Irva Hertz-Picciotto; Deborah H. Bennett (Environmental Research, 2026)

Enhancing reproducibility in neuroimaging with containerized archival - Michael E. Kim; Praitayini Kanakaraj; Yihao Liu; Trent Schwartz; Zhiyuan Li; Nancy R. Newlin; Chenyu Gao; Kurt G. Schilling; Shunxing Bao; Baxter P. Rogers; Bennett A. Landman; Karthik Ramadass (Brain Imaging and Behavior, 2026)
Ensuring reproducibility in scientific research is crucial for validating findings, advancing knowledge, and fostering trust within the scientific community. Containerization of code is a widespread practice to help ensure reproducibility in neuroimaging research. However, there exists no universal method of sharing containers, nor is it feasible to broadly enforce rules due to the diversity of research practices. We posit that container sharing should include 1.) public availability, 2.) self-contained documentation, and 3.) procedures to ensure consistency of the container and its expected outputs. We demonstrate an approach for publicly releasing three separate containers using Zenodo. Our proposed method fulfills the design criteria for container sharing while incurring minimal overhead. As there are several tools available to distribute and maintain containers already, we discuss available alternatives.

Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Description of Skrjabinoclava pharyngophila n. sp. (Nematoda: Acuariidae) from the oropharynx of the sacred kingfisher Todiramphus sanctus (Vigors & Horsfield) in New Zealand - B. Presswell; P. Dorle; I. Scott; J. Bennett (Systematic Parasitology, 2026)
The sacred kingfisher Todiramphus sanctus is a widespread bird species that is non-migratory in New Zealand, in contrast to elsewhere in the world. We describe a new species of Skrjabinoclava , a genus of acuariid nematodes, recovered from the oropharynx of sacred kingfishers in New Zealand. This is the first record of Skrjabinoclava in Australasia and the first publicly available DNA sequence for the genus. Skrjabinoclava pharyngophila n. sp. is unique in its infection site, occupying the oropharyngeal mucosa, which is atypical for Skrjabinoclava species, which usually infect the proventriculus or oesophagus. Morphological and molecular analyses confirm the distinctiveness of this new species, with DNA sequencing placing it within the family Acuariidae. The prevalence of infection was high in North Island birds, while none were found in South Island birds, suggesting the parasite is geographically restricted, possibly due to the distribution of intermediate hosts or the sedentary behavior of the host population. The presence of the parasite in New Zealand sacred kingfishers and its unique infection site offers new insights into the evolution of parasitism in isolated populations.

Gestational exposure to organophosphate ester flame retardants and child growth in weight, height, and body mass index at age 2-10 years: the Environmental influences on Child Health Outcomes Program - Anne P. Starling; Xuan Li; Jennifer L. Ames; Emily S. Barrett; Theresa M. Bastain; Claudia Buss; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Monique M. Hedderson; Julie Herbstman; Kurunthachalam Kannan; et al. (Environmental Research, 2026)

Country readiness for Sargassum valorisation in the Caribbean - M. Bennett; A. March; H. Li; P. Lallemand; J.P. Maréchal; P. Failler (Environmental Development, 2026)

Advancing conservation through virtual livestock fencing - Drew E. Bennett; Travis Brammer; Jerod A. Merkle; Kurt T. Smith; Shawn Regan; Temple Stoellinger; Arthur Middleton; Kristin Barker; Jacob P. Hochard; Patrick E. Lendrum; Erin Welty; Craig Benjamin; et al. (Biological Conservation, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Fasciola gigantica: Ultrastructure and cytochemistry of tegumental secretory activity and extracellular vesicle formation in juvenile flukes migrating in mouse liver - R.E.B. Hanna; G.P. Brennan; M.W. Robinson; P.-E. Kajugu; J.M. Quinn; C.E. Bennett (Veterinary Parasitology, 2026)

Chronic exposure to waterborne nickel significantly reduced growth of juvenile crayfish (Faxonius virilis) - Adrian P. Moore; Mark L. Wildhaber; Zachary D. Beaman; Kendell R. Bennett; Karlie K. Ditter; Danielle Cleveland; Jenna A. Blanton; Tyler J. Grant (Ecotoxicology, 2026)

Evaluating past and future contributions of conservation programs to species recovery - Rebeca E. Young; H. Resit Akçakaya; Elizabeth L. Bennett; Michael Hoffmann; Michael A. Hudson; Barney Long; Thalassa McMurdo Hamilton; Kelsey Neam; Megan A. Owen; Richard P. Young; Molly K. Grace (Conservation Biology, 2026)
Impact evaluation of conservation actions is a crucial step in global efforts to curb the biodiversity crisis. Through robust impact evaluation, practitioners can assess the effectiveness of conservation strategies and optimize the use of limited resources. Despite a proliferation of methods and tools for evaluating conservation impact, no standardized method exists to assess and compare the impact, and global contribution, of species recovery programs. To address this gap, we devised an evaluation framework, based on the International Union for Conservation of Nature (IUCN) Green Status of Species (GSS), a global standard for measuring species recovery. We sought to provide a way for conservation program delivery partners to evaluate the effectiveness of their programs in contributing to global species recovery. We adapted 2 scenarios used in GSS assessments to estimate the impact of worldwide conservation actions on a species (the counterfactual current scenario and the future without conservation scenario), in order to propose a new assessment: the program GSS, a method allowing conservation practitioners to estimate the past and potential future impacts of a conservation program relative to the global impact. To identify the strengths and limitations of applying the GSS method at the program level and to gather proof of concept for our adaptation, we tested the proposed method on 16 species recovery programs. The program GSS approach identified past or future impacts of program actions on species status in 9 of the programs assessed. The detectability of program impact and the relative impact of the program compared with global impact were influenced by time since program establishment and program scope (i.e., proportion of a species’ population or distribution included in the program). Our framework for program GSS assessments can provide practitioners with a standard, straightforward, and cost‐effective way to communicate conservation successes and expected future impacts. Results from our program GSS framework can be compared with the global recovery of a species (conservation legacy and conservation impact) and thus indicate a program's contribution to the recovery of the entire species.

Intense pulsed light treatment for enhancing the storage stability of sorghum flour: lipase inactivation kinetics, fatty acid changes, and shelf-life prediction - N.U. Sruthi; P Srinivasa Rao; Sarita Jane Bennett; Rewati Raman Bhattarai (Journal of Cereal Science, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Prenatal exposure to organophosphate ester flame retardants and child cognition: Findings from the environmental influences on child Health Outcomes cohort - Akhgar Ghassabian; Taylor Etzel; Jennifer L. Ames; Thomas G. O'Connor; Jessie P. Buckley; Sarvenaz Shahin; Julie B. Herbstman; Emily S. Barrett; Donghai Liang; Lisa A. Croen; Rebecca J. Schmidt; Lesliam Quirós-Alcalá; et al. (Environmental Pollution, 2026)

Bomb radiocarbon reveals keratin growth dynamics in loggerhead (Caretta caretta) and green (Chelonia mydas) turtles - Bethan Linscott; Amy A. Wallace; Lorena Becerra-Valdivia; Matt R. P. Harris; Alexandra L. Fireman; Jenna D. Bennett; William F. Patterson; Hannah B. Vander Zanden (Marine Biology, 2026)
Incrementally formed biological tissues can serve as archives of biochemical information pertaining to the life histories of organisms. The sequential isotopic analysis of marine turtle scute keratin is increasingly used for ecological reconstruction, but the timescales represented by these tissues remain poorly understood. Here, we present a method to establish scute growth rates using sequential radiocarbon ( 14 C) measurements on samples taken from loggerhead ( Caretta caretta ) and green turtles ( Chelonia mydas ) stranded along the Florida coast. Using a Δ 14 C coral-otolith reference series and a Bayesian modelling approach, we reconstructed the rate of keratin formation in 24 individuals (representing 120 radiocarbon measurements) and detected synchronous declines in scute growth rates that may be linked to marine environmental stress. Our results provide a chronological framework for the ecological interpretation of biogeochemical data from green and loggerhead turtle scutes and demonstrate the potential for 14 C analysis to investigate the growth dynamics of other incremental tissues.

Gaps in tipping points research across freshwater, marine, and terrestrial ecosystems - Meagan Harper; Charlotte Carrier-Belleau; Trina Rytwinski; Brian Helmuth; Irena F. Creed; John P. Smol; Joseph R. Bennett; Dalal E.L. Hanna; Leonardo A. Saravia; Juan Rocha; Aubrey Foulk; Sam Dupont; et al. (Biological Conservation, 2026)

Epistatic effects of IGHG and FCGRIIB genes on the development of Alzheimer’s disease in African Americans - Janardan P. Pandey; Paul J. Nietert; Aryan M. Namboodiri; David A. Bennett; Lisa L. Barnes (Immunogenetics, 2025)
Genome-wide association studies (GWAS) of Alzheimer’s disease (AD) have identified a large number of susceptibility genes, but most of AD heritability remains unexplained, implying the existence of additional genes. Furthermore, the majority of the GWAS have been conducted in people of European descent, and the genes important for AD susceptibility in people of African descent have been underexplored. In this hypothesis-generating prospective cohort study, we genotyped 191 African Americans (AAs) from three longitudinal cohorts on aging for the IgG3 allotype GM6, which is expressed exclusively in people of African descent, and assessed its interaction with IGHG , FCGRIIB , and HLA-DRB1 genes. Cox proportional hazards modeling showed that GM6 by itself was not significantly associated with AD development. However, there was evidence of epistatic interaction: The risk of developing AD associated with GM6 positivity was significantly different ( p = 0.0098) in non-GM17/GM17 participants compared with GM 17/GM17 participants. Specifically, in non-GM17/GM17 participants, the risk of AD was over fourfold higher in GM6-positive participants compared with GM 6-negative participants (HR = 4.63). Similarly, risk of developing AD associated with GM6 positivity was marginally different in non-FCGRIIB TT participants compared with FCGRIIB TT participants. In non-FCGRIIB TT participants, the risk of developing AD was over twofold higher in GM6-positive participants compared with GM6-negative participants (HR = 2.44). This is the first report suggesting that immunoglobulin GM allotypes might play a role in AD etiology among AAs; however, since this was largely a hypothesis-generating study, replication in larger cohorts would be required to confirm this finding.

High take of mobulid rays in East Java, Indonesia: landing trends and socio-economic context - Betty J. L. Laglbauer; Muhammad G. Salim; Fahmi; Selvia Oktaviyani; Irianies C. Gozali; Firmansyah Tawang; Hasan S. Rizal; Vidlia P. Rosady; Didik Rudianto; Isabel Ender; Jorge M. R. Fontes; Pedro Afonso; et al. (Environmental Biology of Fishes, 2025)

New records of fishes from the Coral Sea Marine Park, Australia - Yi-Kai Tea; Tiffany L. Sih; Fenton Walsh; Timothy Bennett; Luiz A. Rocha; Ghislain Bardout; Amanda Hay; Kerryn Parkinson; Sally Reader; Indiana J. Riley; John J. Pogonoski; Jeffrey W. Johnson; et al. (Coral Reefs, 2025)
With an area covering just under 1 million km 2 , Australia’s Coral Sea Marine Park (CSMP) is among the largest marine protected areas globally. Yet, the demersal deep-reef fish fauna of the CSMP remains poorly described, due in part to its remote location, as well as its sheer size, much of which is inaccessible below conventional SCUBA diving depths. Recent remotely operated vehicle (ROV) explorations conducted by the Schmidt Ocean Institute provided an opportunity to explore the benthic ichthyofauna of deep mesophotic and rariphotic coral ecosystems. Contributions to the deep, demersal ichthyofauna of Australia’s CSMP are herein supplemented with an integrative dataset consisting of ROV imagery and specimen vouchers. Sixty-two new records of fishes from 26 families are reported from the CSMP. Of these, 45 are new Australian records, one of which is also a new family record for Australia. Four species are new records for the Southern Hemisphere, and 21 species are potentially new to science. We report new voucher material for 29 species, including several species previously identified as new for the CSMP with no voucher specimens.

From concept to reality: the journey of establishing the Australian companion animal registry of cancers (ACARCinom) - C. Palmieri; P. Bennett; M. Bruce; M. Krockenberger; P. McLaren; T. Meiring; K. Mengersen; A. Peaston; A. Roach; G. Rossi; A. Stent; R. Soares-Magalhaes (Journal of Comparative Pathology, 2025)

Effect of meal feeding frequency on daytime behavior of individually stalled horses - K.L. Jones; E.R. Share; K. Bennett-Wimbush; J.K. Suagee-Bedore; N.R. Liburt; J.A. Pempek; A. Krotky; B. Cassill; P. Harris; S.L. Mastellar (Journal of Equine Veterinary Science, 2025)

Effect of meal frequency on outdoor, group-housed horse behavior, social hierarchy, and stress - E.R. Share; S.L. Mastellar; J.A. Pempek; K. Bennett-Wimbush; J.K. Suagee-Bedore; N.R. Liburt; A. Krotky; B. Cassill; P. Harris; M.L. Eastridge (Journal of Equine Veterinary Science, 2025)

Qualitative and quantitative assessment of Sargassum valorisation solutions for the Caribbean - M. Bennett; A. March; H. Li; P. Lallemand; J.-P. Maréchal; P. Failler (Journal of Environmental Management, 2025)

Fire Frequency Driven Increases in Burn Heterogeneity Promote Microbial Beta Diversity: A Test of the Pyrodiversity‐Biodiversity Hypothesis - Jacob R. Hopkins; Alison E. Bennett; Thomas P. McKenna (Molecular Ecology, 2025)
Fire is a common ecological disturbance that structures terrestrial ecosystems and biological communities. The ability of fires to contribute to ecosystem heterogeneity has been termed pyrodiversity and has been directly linked to biodiversity (i.e., the pyrodiversity–biodiversity hypothesis). Since climate change models predict increases in fire frequency, understanding how fire pyrodiversity influences soil microbes is important for predicting how ecosystems will respond to fire regime changes. Here we tested how fire frequency‐driven changes in burn patterns (i.e., pyrodiversity) influenced soil microbial communities and diversity. We assessed pyrodiversity effects on soil microbes by manipulating fire frequency (annual vs. biennial fires) in a tallgrass prairie restoration and evaluating how changes in burn patterns influenced microbial communities (bacteria and fungi). Annual burns produced more heterogeneous burn patterns (higher pyrodiversity) that were linked to shifts in fungal and bacterial community composition. While fire frequency did not influence microbial (bacteria and fungi) alpha diversity, beta diversity did increase with pyrodiversity. Changes in fungal community composition were not linked to burn patterns, suggesting that pyrodiversity effects on other ecosystem components (e.g., plants and soil characteristics) influenced fungal community dynamics and the greater beta diversity observed in the annually burned plots. Shifts in bacterial community composition were linked to variation in higher severity burn pattern components (grey and white ash), suggesting that thermotolerance contributed to the observed changes in bacterial community composition and lower beta diversity in the biennially burned plots. This demonstrates that fire frequency‐driven increases in pyrodiversity augment biodiversity and may influence productivity in fire‐prone ecosystems.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

WormRACER: Robust Analysis by Computer-Enhanced Recording - Bennett T. Van Camp; Quinn N. Zapata; Sean P. Curran (GeroScience, 2025)
The pace of scientific high-throughput screening for age-related phenotypes requires the need for developing streamlined and efficacious methods of measuring and quantifying physiological outcomes and at a scale that enables adequate statistical power to measure the variation in populations. Here, we introduce Worm Robust Analysis by Computer-Enhanced Recording (WormRACER), a computationally efficient computer vision software capable of extracting six different crawling and swimming metrics from many animals simultaneously, including worm area, worm length, crawling speed, swimming speed, dynamic amplitude, and wave initiation rate (thrashing). Additionally, we developed a web-based portal that provides metric averages and metric vs time graphs that allow for simple data analysis and quality assurance. WormRACER will facilitate the rapid and quantitative characterization of movement as a facile measurement of healthspan enabling power for high-throughput screening of genetic, environmental, and pharmacological interventions.

A review of 3.7 Ga stromatolites from the Isua Supracrustal Belt, West Greenland - Martin J. Van Kranendonk; Allen P. Nutman; Clark R.L. Friend; Vickie C. Bennett (Earth-Science Reviews, 2025)

Prenatal exposure to environmental bisphenols over time and their association with childhood asthma, allergic rhinitis and atopic dermatitis in the ECHO consortium - Rachel L. Miller; Yuyan Wang; Jenny Aalborg; Akram N. Alshawabkeh; Deborah H. Bennett; Carrie V. Breton; Jessie P. Buckley; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Griffith Gao; Abigail Gaylord; et al. (Environmental Pollution, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Systematic conservation prioritization with the prioritizr R package - Jeffrey O. Hanson; Richard Schuster; Matthew Strimas‐Mackey; Nina Morrell; Brandon P. M. Edwards; Peter Arcese; Joseph R. Bennett; Hugh P. Possingham (Conservation Biology, 2025)
Plans for expanding protected area systems (prioritizations) need to fulfill conservation objectives. They also need to account for other factors, such as economic feasibility and anthropogenic land‐use requirements. Although prioritizations are often generated with decision support tools, most tools have limitations that hinder their use for decision‐making. We outlined how the prioritizr R package ( https://prioritizr.net ) can be used for systematic conservation prioritization. This decision support tool provides a flexible interface to build conservation planning problems. It can leverage a variety of commercial (e.g., Gurobi) and open‐source (e.g., CBC and SYMPHONY) exact algorithm solvers to identify optimal solutions in a short period. It is also compatible with a variety of spatially explicit (e.g., ESRI Shapefile, GeoTIFF) and nonspatial tabular (e.g., Microsoft Excel Spreadsheet) data formats. Additionally, it provides functionality for evaluating prioritizations, such as assessing the relative importance of different places selected by a prioritization. To showcase the prioritizr R package, we applied it to a case study based in Washington state (United States) for which we developed a prioritization to improve protected area coverage of native avifauna. We accounted for land acquisition costs, existing protected areas, places that might not be suitable for protected area establishment, and spatial fragmentation. We also conducted a benchmark analysis to examine the performance of different solvers. The prioritization identified 12,400 km 2 of priority areas for increasing the percentage of species’ distributions covered by protected areas. Although open source and commercial solvers were able to quickly solve large‐scale conservation planning problems, commercial solvers were required for complex, large‐scale problems.. The prioritizr R package is available on the Comprehensive R Archive Network (CRAN). In addition to reserve selection, it can inform habitat restoration, connectivity enhancement, and ecosystem service provisioning. It has been used in numerous conservation planning exercises to inform best practices and aid real‐world decision‐making.

Novel Curvularia species causing disseminated phaeohyphomycosis in a dog - Jared A. Jaffey; Connie F. Cañete-Gibas; Nathan P. Wiederhold; Carmita J. Sanders; Jason D. Struthers; Annalise Black; BinXi Wu; Kara S. Thomas; Patricia Bennett; Jessica Watt (Topics in Companion Animal Medicine, 2025)

Fractionation of complex aromatic hydrocarbon mixtures using membrane cascades hybridized with distillation - Young Joo Lee; Hye Youn Jang; Bennett D. Marshall; Mohammed I.L. Abutaqiya; Neel Rangnekar; Nicholas C. Bruno; M.G. Finn; Ryan P. Lively (Chemical Engineering Journal, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Systematic trends in the substitution mechanisms of minor elements in cassiterite - J. M. Bennett; A. I. S. Kemp; S. G. Hagemann; M. L. Fiorentini; M. P. Roberts (Australian Journal of Earth Sciences, 2024)

Holobiont Traits Shape Climate Change Responses in Cryptic Coral Lineages - Carsten G. B. Grupstra; Kirstin S. Meyer‐Kaiser; Matthew‐James Bennett; Maikani O. Andres; David J. Juszkiewicz; James E. Fifer; Jeric P. Da‐Anoy; Kelly Gomez‐Campo; Isabel Martinez‐Rugerio; Hannah E. Aichelman; Alexa K. Huzar; Annabel M. Hughes; et al. (Global Change Biology, 2024)
As ocean warming threatens reefs worldwide, identifying corals with adaptations to higher temperatures is critical for conservation. Genetically distinct but morphologically similar (i.e. cryptic) coral populations can be specialized to extreme habitats and thrive under stressful conditions. These corals often associate with locally beneficial microbiota (Symbiodiniaceae photobionts and bacteria), obscuring the main drivers of thermal tolerance. Here, we leverage a holobiont (massive Porites ) with high fidelity for C15 photobionts to investigate adaptive variation across classic (“typical” conditions) and extreme reefs characterized by higher temperatures and light attenuation. We uncovered three cryptic lineages that exhibit limited micro‐morphological variation; one lineage dominated classic reefs (L1), one had more even distributions (L2), and a third was restricted to extreme reefs (L3). L1 and L2 were more closely related to populations ~4300 km away, suggesting that some lineages are widespread. All corals harbored Cladocopium C15 photobionts; L1 and L2 shared a photobiont pool that differed in composition between reef types, yet L3 mostly harbored unique photobiont strains not found in the other lineages. Assemblages of bacterial partners differed among reef types in lineage‐specific ways, suggesting that lineages employ distinct microbiome regulation strategies. Analysis of light‐harvesting capacity and thermal tolerance revealed adaptive variation underpinning survival in distinct habitats: L1 had the highest light absorption efficiency and lowest thermal tolerance, suggesting that it is a classic reef specialist. L3 had the lowest light absorption efficiency and the highest thermal tolerance, showing that it is an extreme reef specialist. L2 had intermediate light absorption efficiency and thermal tolerance, suggesting that is a generalist lineage. These findings reveal diverging holobiont strategies to cope with extreme conditions. Resolving coral lineages is key to understanding variation in thermal tolerance among coral populations, can strengthen our understanding of coral evolution and symbiosis, and support global conservation and restoration efforts.

Distribution and time budgets limit occupancy of breeding sites in the nonbreeding season in a colonial seabird - Sophie Bennett; Francis Daunt; Kate R. Searle; Mike P. Harris; Lila Buckingham; James Duckworth; Ruth E. Dunn; Sarah Wanless; Mark A. Newell; Jonathan A. Green (Animal Behaviour, 2024)

Fire season and time since fire determine arbuscular mycorrhizal fungal trait responses to fire - Jacob R. Hopkins; Thomas P. McKenna; Alison E. Bennett (Plant and Soil, 2024)
Background and aims Arbuscular mycorrhizal (AM) fungi are common mutualists in grassland and savanna systems that are adapted to recurrent fire disturbance. This long-term adaptation to fire means that AM fungi display disturbance associated traits which should be useful for understanding environmental and seasonal effects on AM fungal community assembly. Methods In this work, we evaluated how fire effects on AM fungal spore traits and community composition vary with fire season (Fall vs. Spring) and time since fire. We tested this by analyzing AM fungal spore traits (e.g., colorimetric, sporulation, and size) from a fire regime experiment. Results Immediately following Fall and Spring fires, spore pigmentation darkened (became less hyaline); however, this trait response was not linked to fire driven changes in spore community composition and likely implies a plastic spore pigmentation response to fire. Six months after Fall fires, spores in burned plots were lower in volume, produced less color rich pigment, and had higher sporulation rates, and these differences in spore traits were associated with shifts in AM fungal spore communities demonstrating environmental filtering. Conclusion Fire drove plastic and longer-term changes in AM fungal spore traits and community assembly that varied with fire season (stronger effects in Fall) and time since fire. This demonstrates the utility of applying trait-based approaches to microbial community assembly, and the importance of considering changes in community assembly across time.

Functional correlation tensors in brain white matter and the effects of normal aging - Lyuan Xu; Yurui Gao; Muwei Li; Richard Lawless; Yu Zhao; Kurt G. Schilling; Baxter P. Rogers; Adam W. Anderson; Zhaohua Ding; Bennett A. Landman; John C. Gore (Brain Imaging and Behavior, 2024)
Resting state correlations between blood oxygenation level dependent (BOLD) MRI signals from voxels in white matter (WM) are demonstrably anisotropic, so that functional correlation tensors (FCT) may be used to quantify the underlying microstructure of BOLD effects in WM tracts. However, the overall spatial distribution of FCTs and their metrics in specific populations has not yet been established, and the factors that affect their precise arrangements remain unclear. Changes in WM occur with normal aging, and these may be expected to affect FCTs. We hypothesized that FCTs exhibit a characteristic spatial pattern and may show systematic changes with aging or other factors. Here we report our analyses of the FCT characteristics of fMRI images of a large cohort of 461 cognitively normal subjects (190 females, 271 males) sourced from the Open Access Series of Imaging Studies (OASIS), with age distributions of 42 y/o – 95 y/o. Group averages and statistics of FCT indices, including axial functional correlations, radial functional correlations, mean functional correlations and fractional anisotropy, were quantified in WM bundles defined by the JHU ICBM-DTI-81 WM atlas. In addition, their variations with normal aging were examined. The results revealed a dimorphic distribution of changes in FCT metrics with age, with decreases of the functional correlations in some regions and increases in others. Supplementary analysis revealed that females exhibited significant age effects on a greater number of WM areas, but the interaction between age and sex was not significant. The findings demonstrate the reproducibility of the spatial distribution of FCT metrics and reveal subtle regional changes with age.

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Evaluation of registration-based vs. manual segmentation of rhesus macaque brain MRIs - Joey A. Charbonneau; Brittany Davis; Erika P. Raven; Bhakti Patwardhan; Carson Grebosky; Lucas Halteh; Jeffrey L. Bennett; Eliza Bliss-Moreau (Brain Structure and Function, 2024)

Early childhood exposures to phthalates in association with attention-deficit/hyperactivity disorder behaviors in middle childhood and adolescence in the ReCHARGE study - Jiwon Oh; Julie B. Schweitzer; Jessie P. Buckley; Sudhi Upadhyaya; Kurunthachalam Kannan; Julie B. Herbstman; Akhgar Ghassabian; Rebecca J. Schmidt; Irva Hertz-Picciotto; Deborah H. Bennett (International Journal of Hygiene and Environmental Health, 2024)

Exploring the physical and mechanical characteristics of multi-generation recycled aggregate concrete at equivalent compressive strengths - L. Dadd; T. Xie; B. Bennett; P. Visintin (Journal of Cleaner Production, 2024)

Planetary health issues in the developing world: Dynamics between transportation systems, sustainable economic development, and CO2 emissions - Rudra P. Pradhan; Mahendhiran S. Nair; John H. Hall; Sara E. Bennett (Journal of Cleaner Production, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Wet and dry events influenced colonization of a mid-elevation Andean forest - R.A. Sales; C.N.H. McMichael; L.C. Peterson; A. Stanley; I. Bennett; T.E. Jones; A.S. Walker; M. Mulhearn; A. Nelson; C. Moore; M. O'Connor; W. Sinkler; et al. (Quaternary Science Reviews, 2024)

Assessing impacts of a notorious invader (common carp Cyprinus carpio) on Australia's aquatic ecosystems: Coupling abundance-impact relationships with a spatial biomass model - Benjamin G. Fanson; Robin Hale; Jason D. Thiem; Jarod P. Lyon; John D. Koehn; Andrew F. Bennett; Ivor Stuart (Biological Conservation, 2024)

Minimum-entropy velocity estimation from GPS position time series - Jarir Saleh; Richard A. Bennett; Simon D. P. Williams (Journal of Geodesy, 2024)

New Zealand rickettsia‐like organism and Tenacibaculum maritimum vaccine efficacy study - D. Jaramillo; B. P. Busby; M. Bestbier; P. Bennett; Z. Waddington (Journal of Fish Diseases, 2024)
A cohort of Chinook salmon juveniles was vaccinated, with an autogenous bivalent vaccine against New Zealand RLOs (NZ‐RLO1) and Tenacibaculum maritimum. A proportion of the cohort was not vaccinated to act as controls. At smoltification, the fish were challenged with NZ‐RLO1, NZ‐RLO2, or T. maritimum . We found that challenge with T. maritimum by immersion in (7.5 × 10 5 cfu/mL of water) did not yield any pathology. Challenge with RLOs produced clinical signs that were more or less severe depending on the challenge route, dose or vaccination status. Survival was significantly higher for vaccinated fish within the groups challenged with NZ‐RLO1 by intraperitoneal injection with a relative percent survival (RPS) of 48.84%. Survival was not significantly different between vaccinated and non‐vaccinated fish for groups challenged with NZ‐RLO2 by intraperitoneal injection or by NZ‐RLO1 by immersion. Yet, anecdotally the clinical disease presentation (manifesting as haemorrhagic, ulcerative skin lesions) was more severe for the non‐vaccinated fish. This study demonstrates that autogenous vaccine against NZ‐RLO is protective against severe disease and death by NZ‐RLO1 challenge which warrants implementation and further evaluation under field conditions. Yet, this study also highlights the importance of the route of administration and dose when evaluating pathogenicity and vaccine efficacy.

Titanium and iron isotopic records of granitoid crust production in diverse Archean cratons - Zhe J. Zhang; Nicolas Dauphas; Aleisha C. Johnson; Sarah M. Aarons; Vickie C. Bennett; Allen P. Nutman; Scott MacLennan; Blair Schoene (Earth and Planetary Science Letters, 2023)

Evolution of the Palaeozoic mafic-ultramafic Lizard Complex (SW England) from zircon and baddeleyite U-Pb-Hf isotopic constraints: New thoughts on the convergence of Avalonia and Armorica - Allen P. Nutman; Vickie C. Bennett; David H. Green; Clark R.L. Friend (Lithos, 2023)

The biology of an isolated Mashona mole-rat population from southern Malawi, with implications for the diversity and biogeography of the genus Fukomys - R. Šumbera; M. Uhrová; S. Begall; K. R. Caspar; D. Jerkovičová; P. Van Daele; W. N. Chitaukali; C. G. Faulkes; N. C. Bennett; C. Johannes; H. Burda; O. Mikula (Organisms Diversity & Evolution, 2023)
The Mashona mole-rat, Fukomys darlingi (Thomas, 1895), is a little studied social African mole-rat (Bathyergidae) from south-astern Africa. Here, we present an integrative study characterizing the genetic diversity of populations assigned to F. darlingi with special focus on animals from Nsanje, southern Malawi. These mole-rats show pronounced differences in body mass and general appearance compared to nominate F. darlingi from Zimbabwe and Mozambique, but their taxonomic status has so far remained unclear. A genetic analysis encompassing all major lineages of the genus Fukomys suggests that this population indeed represents a deeply nested lineage within the F. darlingi clade . The karyotype of the Nsanje mole-rats also corresponds to that of the nominate form, being 2n = 54. While both nuclear and mitochondrial data agree about the assignment of the Nsanje mole-rats to F. darlingi , our analyses revealed substantial mitonuclear discordance for other branches within the Fukomys phylogenetic tree. Nsanje mole-rats are significantly larger than nominate F. darlingi and their ontogeny and reproduction closely resemble similar-sized congeneric species rather than the nominate population. The somatic growth of the Nsanje form is the slowest of all African mole-rats. The maximum life span of F. darlingi is at least 19 years. The observed differences between nominate F. darlingi and mole-rats from Nsanje may be attributed mainly to their different body mass. Our study highlights the advantages of an integrative approach for understanding the diversity of African mole-rats and emphasizes the great intraspecific variability that may be encountered in these underground-dwelling rodents.

Valorisation strategies for brown seaweed biomass production in a European context - Joseph P. Bennett; Laura F. Robinson; Leonardo D. Gomez (Algal Research, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Modelling compound flooding: a case study from Jakarta, Indonesia - William G. Bennett; Harshinie Karunarathna; Yunqing Xuan; Muhammad S. B. Kusuma; Mohammad Farid; Arno A. Kuntoro; Harkunti P. Rahayu; Benedictus Kombaitan; Deni Septiadi; Tri N. A. Kesuma; Richard Haigh; Dilanthi Amaratunga (Natural Hazards, 2023)
The paper investigates compound flooding from waves, sea surge and river flow in northern Jakarta, Indonesia, which is a global hotspot of flooding, by combining process-based coastal and river models. The coastal hydrodynamic modelling of Jakarta Bay in Indonesia shows that coastal storms can lead to a substantial increase in sea water level due to wind and wave setup in the nearshore areas, including Muara Angke river inlet. The compound flood hazard from a range of flood scenarios was simulated and analysed. The results reveal that low-lying areas around the river inlet are prone to flooding even during regular, low-intensity storm events, while rarer storms caused extensive floods. Floods were not caused by direct overwashing of sea defences but by overspill of the banks of the river inlet due to high sea water level caused by wind set up, wave setup, and sea surge obstructing the drainage of the river and elevating its water level during storms. We also found that the sea level rise combined with rapid land subsidence will inundate the existing coastal flood defences during storms in future. The majority of the city will be below mean sea level by 2100. The overflow of existing coastal defences will lead to extensive flooding in northern, western, and eastern Jakarta unless the defences are upgraded to keep up with future sea level rise.

The IV International Symposium on Fungal Stress and the XIII International Fungal Biology Conference - Alene Alder-Rangel; Alexandre Melo Bailão; Alfredo Herrera-Estrella; Amanda E.A. Rangel; Attila Gácser; Audrey P. Gasch; Claudia B.L. Campos; Christina Peters; Francine Camelim; Fulvia Verde; Geoffrey Michael Gadd; Gerhard Braus; et al. (Fungal Biology, 2023)

Acrylic acid and DMSP lyases in the green algae Ulva - Giovanna Pesante; Edith Forestier; Swen Langer; Andrew Danby; John Angus; Mark Gronnow; Joseph P. Bennett; Tony R. Larson; Thierry Tonon (Algal Research, 2023)

Quantifying the impacts of predation by Great Black-backed Gulls Larus marinus on an Atlantic Puffin Fratercula arctica population: Implications for conservation management and impact assessments - Samuel Langlois Lopez; Francis Daunt; Jared Wilson; Nina J. O'Hanlon; Kate R. Searle; Sophie Bennett; Mark A. Newell; Michael P. Harris; Elizabeth Masden (Marine Environmental Research, 2023)

Protected area planning to conserve biodiversity in an uncertain future - Richard Schuster; Rachel Buxton; Jeffrey O. Hanson; Allison D. Binley; Jeremy Pittman; Vivitskaia Tulloch; Frank A. La Sorte; Patrick R. Roehrdanz; Peter H. Verburg; Amanda D. Rodewald; Scott Wilson; Hugh P. Possingham; et al. (Conservation Biology, 2023)
Protected areas are a key instrument for conservation. Despite this, they are vulnerable to risks associated with weak governance, land‐use intensification, and climate change. We used a novel hierarchical optimization approach to identify priority areas for expanding the global protected area system that explicitly accounted for such risks while maximizing protection of all known terrestrial vertebrate species. To incorporate risk categories, we built on the minimum set problem, where the objective is to reach species distribution protection targets while accounting for 1 constraint, such as land cost or area. We expanded this approach to include multiple objectives accounting for risk in the problem formulation by treating each risk layer as a separate objective in the problem formulation. Reducing exposure to these risks required expanding the area of the global protected area system by 1.6% while still meeting conservation targets. Incorporating risks from weak governance drove the greatest changes in spatial priorities for protection, and incorporating risks from climate change required the largest increase (2.52%) in global protected area. Conserving wide‐ranging species required countries with relatively strong governance to protect more land when they bordered nations with comparatively weak governance. Our results underscore the need for cross‐jurisdictional coordination and demonstrate how risk can be efficiently incorporated into conservation planning. Planeación de las áreas protegidas para conservar la biodiversidad en un futuro incierto

Patterns of community science data use in peer-reviewed research on biodiversity - A.D. Binley; J.G. Vincent; T. Rytwinski; C.A. Proctor; E.S. Urness; S.A. Davis; P. Soroye; J.R. Bennett (Biological Conservation, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Does atmospheric dimethyldiselenide play a role in reducing COVID-19 mortality? - Jinsong Zhang; Ethan Will Taylor; Kate Bennett; Margaret P. Rayman (Gondwana Research, 2023)

Dose metric evaluation of a cell-based bioassay for assessing the toxicity of metals to Dugong dugon: Effect of metal-media interactions on exposure concentrations - David Bailey; Kimberly A. Finlayson; Gulsah Dogruer; William W. Bennett; Jason P. van de Merwe (Aquatic Toxicology, 2023)

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

Rank change and growth within social hierarchies of the orange clownfish, Amphiprion percula - L. M. Fitzgerald; H. B. Harrison; D. J. Coker; P. Sáenz-Agudelo; M. Srinivasan; J. E. Majoris; L. Boström Einarsson; B. Pujol; M. Bennett-Smith; S. R. Thorrold; S. Planes; G. P. Jones; et al. (Marine Biology, 2022)
Social hierarchies within groups define the distribution of resources and provide benefits that support the collective group or favor dominant members. The progression of individuals through social hierarchies is a valuable characteristic for quantifying population dynamics. On coral reefs, some clownfish maintain size-based hierarchical communities where individuals queue through social ranks. The cost of waiting in a lower-ranked position is outweighed by the reduced risk of eviction and mortality. The orange clownfish, Amphiprion percula , maintains stable social groups with subordinate individuals queuing to be part of the dominant breeding pair. Strong association with their host anemone, complex social interactions, and relatively low predation rates make them ideal model organisms to assess changes in group dynamics through time in their natural environment. Here, we investigate the rank changes and isometric growth rates of A. percula from 247 naturally occurring social groups in Kimbe Island, Papua New Guinea (5° 12′ 13.54″ S, 150° 22′ 32.69″ E). We used DNA profiling to assign and track individuals over eight years between 2011 and 2019. Over half of the individuals survived alongside two or three members of their original social group, with twelve breeding pairs persisting over the study period. Half of the surviving individuals increased in rank and experienced double the growth rate of those that maintained their rank. Examining rank change in a wild fish population provides new insights into the complex social hierarchies of reef fishes and their role in social evolution.

Plant responses to soil biota depend on precipitation history, plant diversity, and productivity - Seth Lundell; Amgaa Batbaatar; Cameron N. Carlyle; Eric G. Lamb; Rafael Otfinowski; Michael P. Schellenberg; Jonathan A. Bennett (Ecology, 2022)
Soil biota are critical drivers of plant growth, population dynamics, and community structure and thus have wide‐ranging effects on ecosystem function. Interactions between plants and soil biota are complex, however, and can depend on the diversity and productivity of the plant community and environmental conditions. Plant–soil biota interactions may be especially important during stressful periods, such as drought, when plants can gain great benefits from beneficial biota but may be susceptible to antagonists. How soil biota respond to drought is also important and can influence plant growth following drought and leave legacies that affect future plant responses to soil biota and further drought. To explore how drought legacies and plant community context influence plant growth responses to soil biota and further drought, we collected soils from 12 grasslands varying in plant diversity and productivity where precipitation was experimentally reduced. We used these soils as inoculum in a growth chamber experiment testing how precipitation history (ambient or reduced) and soil biota (live or sterile soil inoculum) mediate plant growth and drought responses within an experimental plant community. We also tested whether these responses differed with the diversity and productivity of the community where the soil was collected. Plant growth responses to soil biota were positive when inoculated with soils from less diverse and productive plant communities and became negative as the diversity and productivity of the conditioning community increased. At low diversity, however, positive soil biota effects on plant growth were eliminated if precipitation had been reduced in the field, suggesting that diversity loss may heighten climate change sensitivity. Differences among species within the experimental community in their responses to soil biota and drought suggest that species benefitting from less drought sensitive soil biota may be able to compensate for some of this loss of productivity. Regardless of the plant species and soil origin, further drought eliminated any effects of soil biota on plant growth. Consequently, soil biota may be unable to buffer the effects of drought on primary productivity or other ecosystem functions as extreme events increase in frequency.

The influence of regions of interest on tractography virtual dissection protocols: general principles to learn and to follow - Francois Rheault; Kurt G. Schilling; Sami Obaid; John P. Begnoche; Laurie E. Cutting; Maxime Descoteaux; Bennett A. Landman; Laurent Petit (Brain Structure and Function, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Evaluation of Gonad Reproductive Condition Using Non-invasive Ultrasonography in Red Abalone (Haliotis rufescens) - Sara E. Boles; Isabelle P. Neylan; Laura Rogers-Bennett; Jackson A. Gross (Frontiers in Marine Science, 2022)
The reproductive status in abalone ( Haliotis spp.) can be difficult to discern using traditional visual inspection methods and may therefore rely on lethal histological analyses for a definitive determination. With endangered species of abalone, lethal histological examinations are strictly prohibited due to their imperiled status. This research investigated the effectiveness of using non-invasive ultrasound technology as an alternate means of identifying the reproductive status of abalone rather than through invasive biopsies or lethal histological methods. Twelve abalone were randomly selected from cultured red abalone broodstock cohort ( n = 200) produced at The Cultured Abalone Farm (Goleta, CA) to initially test these methods. Following initial gonad ultrasound determination, a subset of another cohort of 5 year-old ( n = 62) red abalone produced at the UC Davis Bodega Marine Laboratory were monitored using ultrasonography to detect seasonal changes in gonad size for 7 weeks. Following the 7-week assessment period, the full cohort of 5-year old abalone ( n = 122) were then spawned and gonads were also evaluated using ultrasound technology before and immediately after spawning. Ultrasound imaging technology accurately differentiated between digestive and reproductive tissues, allowing for the characterization of an ultrasound gonad index score for rapid assessment. Mean gonad thickness determined via ultrasound imaging was categorized on a scale of 1–5, with an index of 1 being the lowest (gonad tissue thin or absent) and an index of 5 being the highest (gonad margin has increased and is compressing the digestive gland) for red abalone. Ultrasound imaging technology was successful in rendering a gonad index score that can be used to track gonad maturation over time in cultured or captive species. Tracking ultrasound gonad scores over time is a useful tool for improving abalone culture production, and increasing animal welfare by reducing handling stress associated with gonad assessments. Individual abalone that are empirically determined ready to be spawned can then be selected for broodstock. Non-invasive ultrasound technology has the potential for broad applications within abalone aquaculture to enhance both food and conservation aquaculture breeding programs.

Impact of cocoa agricultural intensification on bird diversity and community composition - Ruth E. Bennett; T. Scott Sillett; Robert A. Rice; Peter P. Marra (Conservation Biology, 2022)
To meet the growing demand for chocolate, cocoa ( Theobroma cacao ) agriculture is expanding and intensifying. Although this threatens tropical forests, cocoa sustainability initiatives largely overlook biodiversity conservation. To inform these initiatives, we analyzed how cocoa agriculture affects bird diversity at farm and landscape scales with a meta‐analysis of 23 studies. We extracted 214 Hedges' g * comparisons of bird diversity and 14 comparisons of community similarity between a forest baseline and 4 farming systems that cover an intensification gradient in landscapes with high and low forest cover, and we summarized 119 correlations between cocoa farm features and bird diversity. Bird diversity declined sharply in low shade cocoa. Cocoa with >30% canopy cover from diverse trees retained bird diversity similar to nearby primary or mature secondary forest but held a different community of birds. Diversity of endemic species, frugivores, and insectivores (agriculture avoiders) declined, whereas diversity of habitat generalists, migrants, nectarivores, and granivores (agriculture associates) increased. As forest decreased on the landscape, the difference in bird community composition between forest and cocoa also decreased, indicating agriculture associates replaced agriculture avoiders in forest patches. Our results emphasize the need to conserve forested landscapes (land sparing) and invest in mixed‐shade agroforestry (land sharing) because each strategy benefits a diverse and distinct biological community.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Thermal optima of gross primary productivity are closely aligned with mean air temperatures across Australian wooded ecosystems - Alison C. Bennett; Stefan K. Arndt; Lauren T. Bennett; Jürgen Knauer; Jason Beringer; Anne Griebel; Nina Hinko‐Najera; Michael J. Liddell; Daniel Metzen; Elise Pendall; Richard P. Silberstein; Timothy J. Wardlaw; et al. (Global Change Biology, 2021)
Gross primary productivity (GPP) of wooded ecosystems (forests and savannas) is central to the global carbon cycle, comprising 67%–75% of total global terrestrial GPP. Climate change may alter this flux by increasing the frequency of temperatures beyond the thermal optimum of GPP ( T opt ). We examined the relationship between GPP and air temperature (Ta) in 17 wooded ecosystems dominated by a single plant functional type (broadleaf evergreen trees) occurring over a broad climatic gradient encompassing five ecoregions across Australia ranging from tropical in the north to Mediterranean and temperate in the south. We applied a novel boundary‐line analysis to eddy covariance flux observations to (a) derive ecosystem GPP–Ta relationships and T opt (including seasonal analyses for five tropical savannas); (b) quantitatively and qualitatively assess GPP–Ta relationships within and among ecoregions; (c) examine the relationship between T opt and mean daytime air temperature (MDTa) across all ecosystems; and (d) examine how down‐welling short‐wave radiation (Fsd) and vapour pressure deficit (VPD) influence the GPP–Ta relationship. GPP–Ta relationships were convex parabolas with narrow curves in tropical forests, tropical savannas (wet season), and temperate forests, and wider curves in temperate woodlands, Mediterranean woodlands, and tropical savannas (dry season). Ecosystem T opt ranged from 15℃ (temperate forest) to 32℃ (tropical savanna—wet and dry seasons). The shape of GPP–Ta curves was largely determined by daytime Ta range, MDTa, and maximum GPP with the upslope influenced by Fsd and the downslope influenced by VPD. Across all ecosystems, there was a strong positive linear relationship between T opt and MDTa (Adjusted R 2 : 0.81; Slope: 1.08) with T opt exceeding MDTa by >1℃ at all but two sites. We conclude that ecosystem GPP has adjusted to local MDTa within Australian broadleaf evergreen forests and that GPP is buffered against small Ta increases in the majority of these ecosystems.

Novel ferrocenyl chalcone derivatives as antibacterial agents: is there a solution to the problem? - Elecia J. Henry; Charles Thomas Bennett; Michael Collins; John P. Cassella (Medicinal Chemistry Research, 2021)

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

Impact of changes in controlled drugs legislation on benzodiazepine receptor agonist prescribing in Ireland: a repeated cross-sectional study - Cathal A. Cadogan; Colin P. Bradley; Kathleen Bennett (European Journal of Clinical Pharmacology, 2021)
Purpose To examine the impact of new controlled drugs legislation introduced in May 2017 on benzodiazepine receptor agonist (BZRA) prescribing in Ireland. Methods A repeated cross-sectional analysis was conducted using publically available monthly pharmacy claims data from the General Medical Services (GMS) database. The study population comprised all GMS-eligible individuals aged ≥ 16 years from January 2016 to September 2019. Monthly prevalence rates of individuals receiving BZRA prescriptions per 10,000 eligible population were calculated and trends examined over time. Segmented linear regression of prevalence rates was used to examine changes before and after introduction of the legislation stratified by gender and age groups. Regression coefficients (β) and 95% confidence intervals (CIs) for monthly change were calculated. Results Pre-legislation (January 2016 to April 2017), there was a significant monthly decline in benzodiazepine prevalence rate (β = − 1.18; 95% CI − 1.84, − 0.51; p < 0.001) but no significant change in Z-drug prescribing. Post-legislation (May 2017 to September 2019), increases in prevalence rates were observed for benzodiazepines (β = 1.04; 95% CI 0.17, 1.92; p = 0.021) and Z-drugs (β = 1.04; 95% CI 0.26, 1.83; p = 0.010). Post-legislation trends showed increases in BZRA prevalence rates among the youngest subgroup (16–44 years), with variable changes in the middle-aged subgroup (45–64 years) and no changes in the oldest subgroup (≥ 65 years). Conclusions This study indicates that introduction of new legislation had limited impact on BZRA prescribing on the main public health scheme in Ireland. Interventions targeting specific population subgroups may be required to achieve sustained reductions in prescribing.

Caveolin-1 is Involved in Regulating the Biological Response of Cells to Nanosecond Pulsed Electric Fields - Jody C. Cantu; Gleb P. Tolstykh; Melissa Tarango; Hope T. Beier; Bennett L. Ibey (The Journal of Membrane Biology, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Correction to: Addition of nectar sources affects a parasitoid community without improving pest suppression - Jacob H. Miall; Paul K. Abram; Naomi Cappuccino; Andrew M. R. Bennett; José L. Fernández-Triana; Gary A. P. Gibson; Peter G. Mason (Journal of Pest Science, 2021)

Addition of nectar sources affects a parasitoid community without improving pest suppression - Jacob H. Miall; Paul K. Abram; Naomi Cappuccino; Andrew M. R. Bennett; José L. Fernández-Triana; Gary A. P. Gibson; Peter G. Mason (Journal of Pest Science, 2021)

Elemental Metabolomics for Prediction of Term Gestational Outcomes Utilising 18-Week Maternal Plasma and Urine Samples - Daniel R. McKeating; Vicki L. Clifton; Cameron P. Hurst; Joshua J. Fisher; William W. Bennett; Anthony V. Perkins (Biological Trace Element Research, 2021)

A cross‐scale assessment of productivity–diversity relationships - Dylan Craven; Masha T. van der Sande; Carsten Meyer; Katharina Gerstner; Joanne M. Bennett; Darren P. Giling; Jes Hines; Helen R. P. Phillips; Felix May; Katherine H. Bannar‐Martin; Jonathan M. Chase; Petr Keil (Global Ecology and Biogeography, 2020)
Aim Biodiversity and ecosystem productivity vary across the globe, and considerable effort has been made to describe their relationships. Biodiversity and ecosystem functioning research has traditionally focused on how experimentally controlled species richness affects net primary productivity ( S → NPP) at small spatial grains. In contrast, the influence of productivity on richness (NPP → S ) has been explored at many grains in naturally assembled communities. Mismatches in spatial scale between approaches have fuelled debate about the strength and direction of biodiversity–productivity relationships. Here, we examine the direction and strength of the influence of productivity on diversity (NPP → S ) and the influence of diversity on productivity ( S → NPP) and how these vary across spatial grains. Location Contiguous USA. Time period 1999–2015. Major taxa studied Woody species (angiosperms and gymnosperms). Methods Using data from North American forests at grains from local (672 m 2 ) to coarse spatial units (median area = 35,677 km 2 ), we assess relationships between diversity and productivity using structural equation and random forest models, while accounting for variation in climate, environmental heterogeneity, management and forest age. Results We show that relationships between S and NPP strengthen with spatial grain. Within each grain, S → NPP and NPP → S have similar magnitudes, meaning that processes underlying S → NPP and NPP → S either operate simultaneously or that one of them is real and the other is an artefact. At all spatial grains, S was one of the weakest predictors of forest productivity, which was largely driven by biomass, temperature and forest management and age. Main conclusions We conclude that spatial grain mediates relationships between biodiversity and productivity in real‐world ecosystems and that results supporting predictions from each approach (NPP → S and S → NPP) serve as an impetus for future studies testing underlying mechanisms. Productivity–diversity relationships emerge at multiple spatial grains, which should widen the focus of national and global policy and research to larger spatial grains.

Age-based changes in kairomone response mediate task partitioning in stingless bee soldiers (Tetragonisca angustula) - Kaitlin M. Baudier; Meghan M. Bennett; Madeleine M. Ostwald; Sarah Hart; Theodore P. Pavlic; Jennifer H. Fewell (Behavioral Ecology and Sociobiology, 2020)

The Fe-type nitrile hydratase from Rhodococcus equi TG328-2 forms an alpha-activator protein complex - K. P. Wasantha Lankathilaka; Brian Bennett; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2020)

A dosimetric comparison of flattening filter free and conventional VMAT treatments for some common cancer sites - J. P. Ronaldson; H. Bennett; J. Roberts; A. J. Ronaldson; A. T. Cousins (Physical and Engineering Sciences in Medicine, 2020)

Computational Modelling of the Impacts of Saltmarsh Management Interventions on Hydrodynamics of a Small Macro-Tidal Estuary - William G. Bennett; Thomas J. van Veelen; Tom P. Fairchild; John N. Griffin; Harshinie Karunarathna (Journal of Marine Science and Engineering, 2020)
Saltmarshes are considered as natural coastal defences. However, owing to the large context dependency, there is much discussion over their effectiveness in providing coastal protection and the necessity of additional coastal defence interventions. The macro-tidal Taf Estuary in south-west Wales was chosen as the case study in this paper to investigate the effects of anthropogenic coastal defence interventions such as construction of hard defences, managed realignment, and altering land use of the saltmarshes on the complex hydrodynamics of the estuary. A coupled flow–wave–vegetation model, developed using the Delft3D coastal modelling software, was used. The wave and current attenuation role of saltmarshes during two contrasting storm conditions was modelled, with and without saltmarsh management interventions. The study reveals that certain saltmarsh management interventions can have widespread impacts on the hydrodynamics of the estuary. Altering the land use by allowing extensive grazing of saltmarsh by livestock was found to have the largest impact on wave attenuation, where wave heights on the marsh almost doubled when compared with the no-intervention scenario. On the other hand, managed realignment has a significant impact on tidal currents, where tidal currents reached 0.5 m/s at certain locations. Changes in estuarine hydrodynamics can lead to undesired impacts on flooding and erosion, which stresses the importance of understanding the effects of localized anthropogenic coastal management interventions on the entire estuarine system.

Evaluation of potential human health risk associated with consumption of edible products from livestock fed ration supplemented with Red Lake Diatomaceous Earth - Daniele S. Wikoff; Darin C. Bennett; Gregory P. Brorby; Kara S. Franke (Food Additives & Contaminants: Part A, 2020)

Photoperiodic effects on the male gonads of the Namibian gerbil, Gerbilliscus cf. leucogaster from central Namibia - Sachariah P. Muteka; Christian T. Chimimba; Armanda D. S. Bastos; Nigel C. Bennett (Mammalian Biology, 2020)

Seeds of good anthropocenes: developing sustainability scenarios for Northern Europe - C. Raudsepp-Hearne; G. D. Peterson; E. M. Bennett; R. Biggs; A. V. Norström; L. Pereira; J. Vervoort; D. M. Iwaniec; T. McPhearson; P. Olsson; T. Hichert; M. Falardeau; et al. (Sustainability Science, 2020)

Status and trends in Arctic vegetation: Evidence from experimental warming and long-term monitoring - Anne D. Bjorkman; Mariana García Criado; Isla H. Myers-Smith; Virve Ravolainen; Ingibjörg Svala Jónsdóttir; Kristine Bakke Westergaard; James P. Lawler; Mora Aronsson; Bruce Bennett; Hans Gardfjell; Starri Heiðmarsson; Laerke Stewart; et al. (Ambio, 2020)

Cellular maturation of an iron-type nitrile hydratase interrogated using EPR spectroscopy - K. P. Wasantha Lankathilaka; Natalia Stein; Richard C. Holz; Brian Bennett (JBIC Journal of Biological Inorganic Chemistry, 2019)

National contributions to global ecosystem values - Laura E. Coristine; Sheila Colla; Nathan Bennett; Anja M. Carlsson; Christina Davy; Kimberley T.A. Davies; Brett Favaro; D.T. Tyler Flockhart; Kevin Fraser; Diane Orihel; Sarah P. Otto; Wendy Palen; et al. (Conservation Biology, 2019)
Current conservation templates prioritize biogeographic regions with high intensity ecosystem values, such as exceptional species richness or threat. Intensity‐based targets are an important consideration in global efforts, but they do not capture all available opportunities to conserve ecosystem values, including those that accrue in low intensity over large areas. We assess six globally‐significant ecosystem values—intact wilderness, freshwater availability, productive marine environments, breeding habitat for migratory wildlife, soil carbon storage, and latitudinal potential for range shift in the face of climate change—to highlight opportunities for high‐impact broadly‐distributed contributions to global conservation. Nations can serve as a cohesive block of policy that can profoundly influence conservation outcomes. Contributions to global ecosystem values that exceed what is predicted by a nation's area alone, can give rise to countries with the capacity to act as ‘conservation superpowers’, such as Canada and Russia. For these conservation superpowers, a relatively small number of national policies can have environmental repercussions for the rest of the world.

Polyphenol-associated oxidative stress and inflammation in a model of LPS-induced inflammation in glial cells: do we know enough for responsible compounding? - Guillermo Cásedas; Amber C. Bennett; E. González-Burgos; M. P. Gómez-Serranillos; Víctor López; Carine Smith (Inflammopharmacology, 2019)

Watershed Buffering of Legacy Phosphorus Pressure at a Regional Scale: A Comparison Across Space and Time - A. S. Kusmer; J.-O. Goyette; G. K. MacDonald; E. M. Bennett; R. Maranger; P. J. A. Withers (Ecosystems, 2019)

Rare loss of function variants in candidate genes and risk of colorectal cancer - Elisabeth A. Rosenthal; Brian H. Shirts; Laura M. Amendola; Martha Horike-Pyne; Peggy D. Robertson; Fuki M. Hisama; Robin L. Bennett; Michael O. Dorschner; Deborah A. Nickerson; Ian B. Stanaway; Rami Nassir; Kathy T. Vickers; et al. (Human Genetics, 2018)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Pharmacodynamic and Pharmacokinetic Properties of AFPep, a Novel Peptide for the Treatment of Breast Cancer - J. A. Bennett; W. Mansouri; Q. Lin; P. Feustel; T. T. Andersen (International Journal of Peptide Research and Therapeutics, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

The recalibration of tactile perception during tool use is body-part specific - Luke E. Miller; Andrew Cawley-Bennett; Matthew R. Longo; Ayse P. Saygin (Experimental Brain Research, 2017)

Four Biofuel Species’ Responses to Periodic Flooding and High Water Tables on a Florida Histosol - Stephen P. Jennewein; Robert A. Gilbert; Diane L. Rowland; Alan L. Wright; Barry Glaz; Jerry M. Bennett (BioEnergy Research, 2017)

Impact of Fiber Structure on the Material Stability and Rupture Mechanisms of Coronary Atherosclerotic Plaques - Graeham R. Douglas; Adam J. Brown; Jonathan H. Gillard; Martin R. Bennett; Michael P. F. Sutcliffe; Zhongzhao Teng (Annals of Biomedical Engineering, 2017)

Philopatry and dispersal of juvenile leervis Lichia amia (Teleostei: Carangidae) tagged in a warm-temperate South African estuary - T Murray; P Cowley; A-R Childs; R Bennett (African Journal of Marine Science, 2017)

Genetic stock structure of white steenbras Lithognathus lithognathus (Cuvier, 1829), an overexploited fishery species in South African waters - RH Bennett; K Reid; G Gouws; P Bloomer; PD Cowley (African Journal of Marine Science, 2017)

Reproductive parameters of rhinobatid and urolophid batoids taken as by‐catch in the Queensland (Australia) east coast otter‐trawl fishery - P. M. Kyne; A. J. Courtney; I. P. Jacobsen; M. B. Bennett (Journal of Fish Biology, 2016)
Reproductive variables are provided for batoids regularly taken as by‐catch in the east coast otter‐trawl fishery on the inner‐mid continental shelf off the south‐east and central coasts of Queensland, Australia. Total length at maturity ( L T50 and 95% c.i .) for the eastern shovelnose ray Aptychotrema rostrata was 639·5 mm (617·6–663·4 mm) for females and 597·3 mm (551·4–648·6 mm) for males. Litter size ( n = 9) ranged from nine to 20 (mean ± s.e. = 15·1 ± 1·2). This species exhibited a positive litter size–maternal size relationship. Disc width at maturity ( W D50 and 95% c.i .) for the common stingaree Trygonoptera testacea was 162·7 mm (155·8–168·5 mm) for females and 145·9 mm (140·2–150·2 mm) for males. Gravid T. testacea ( n = 6) each carried a single egg in the one functional (left) uterus. Disc width at maturity ( W D50 and 95% c.i .) for the Kapala stingaree Urolophus kapalensis was 153·7 mm (145·1–160·4 mm) for females and 155·2 mm (149·1–159·1 mm) for males. Gravid U. kapalensis ( n = 16) each carried a single egg or embryo in the one functional (left) uterus. A single female yellowback stingaree Urolophus sufflavus carried an embryo in each uterus. A global review of the litter sizes of shovelnose rays (Rhinobatidae) and stingarees (Urolophidae) is provided.

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

Unpacking Pandora’s Box: Understanding and Categorising Ecosystem Disservices for Environmental Management and Human Wellbeing - C. M. Shackleton; S. Ruwanza; G. K. Sinasson Sanni; S. Bennett; P. De Lacy; R. Modipa; N. Mtati; M. Sachikonye; G. Thondhlana (Ecosystems, 2016)

Age and growth of the tiger shark Galeocerdo cuvier off the east coast of Australia - B. J. Holmes; V. M. Peddemors; A. N. Gutteridge; P. T. Geraghty; R. W. K. Chan; I. R. Tibbetts; M. B. Bennett (Journal of Fish Biology, 2015)
Total lengths ( L T ) at age and growth rates for south‐west Pacific Galeocerdo cuvier were estimated from vertebral growth‐band counts of 202 sagitally sectioned centra from 112 females (71–430 cm L T ), 79 males (72–351 cm L T ) and 11 of unknown sex. Captive growth data were also examined to complement vertebral age estimations. The sexes combined modelled growth coefficient ( k = 0·08) was smaller than previously reported for G. cuvier populations elsewhere. Split‐band and narrow banding patterns were identified as potential sources of age underestimation in this species.

Using Flow-Ecology Relationships to Evaluate Ecosystem Service Trade-Offs and Complementarities in the Nation’s Largest River Swamp - Justin P. Kozak; Micah G. Bennett; Anne Hayden-Lesmeister; Kelley A. Fritz; Aaron Nickolotsky (Environmental Management, 2015)

Effect of risk aversion on prioritizing conservation projects - Ayesha I.T. Tulloch; Richard F. Maloney; Liana N. Joseph; Joseph R. Bennett; Martina M.I. Di Fonzo; William J.M. Probert; Shaun M. O'Connor; Jodie P. Densem; Hugh P. Possingham (Conservation Biology, 2015)
Conservation outcomes are uncertain. Agencies making decisions about what threat mitigation actions to take to save which species frequently face the dilemma of whether to invest in actions with high probability of success and guaranteed benefits or to choose projects with a greater risk of failure that might provide higher benefits if they succeed. The answer to this dilemma lies in the decision maker's aversion to risk—their unwillingness to accept uncertain outcomes. Little guidance exists on how risk preferences affect conservation investment priorities. Using a prioritization approach based on cost effectiveness, we compared 2 approaches: a conservative probability threshold approach that excludes investment in projects with a risk of management failure greater than a fixed level, and a variance‐discounting heuristic used in economics that explicitly accounts for risk tolerance and the probabilities of management success and failure. We applied both approaches to prioritizing projects for 700 of New Zealand's threatened species across 8303 management actions. Both decision makers’ risk tolerance and our choice of approach to dealing with risk preferences drove the prioritization solution (i.e., the species selected for management). Use of a probability threshold minimized uncertainty, but more expensive projects were selected than with variance discounting, which maximized expected benefits by selecting the management of species with higher extinction risk and higher conservation value. Explicitly incorporating risk preferences within the decision making process reduced the number of species expected to be safe from extinction because lower risk tolerance resulted in more species being excluded from management, but the approach allowed decision makers to choose a level of acceptable risk that fit with their ability to accommodate failure. We argue for transparency in risk tolerance and recommend that decision makers accept risk in an adaptive management framework to maximize benefits and avoid potential extinctions due to inefficient allocation of limited resources. El Efecto de la Aversión de Riesgo sobre la Priorización de Proyectos de Conservación

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Effects of Antibiotic Physicochemical Properties on Their Release Kinetics from Biodegradable Polymer Microparticles - Sarita R. Shah; Allan M. Henslee; Patrick P. Spicer; Shun Yokota; Sophia Petrichenko; Sachin Allahabadi; George N. Bennett; Mark E. Wong; F. Kurtis Kasper; Antonios G. Mikos (Pharmaceutical Research, 2014)

Mitochondrial Oxidative Phosphorylation Transcriptome Alterations in Human Amyotrophic Lateral Sclerosis Spinal Cord and Blood - Amy C. Ladd; Paula M. Keeney; Maria M. Govind; James P. Bennett (NeuroMolecular Medicine, 2014)

Tiger shark (Galeocerdo cuvier) movement patterns and habitat use determined by satellite tagging in eastern Australian waters - Bonnie J. Holmes; Julian G. Pepperell; Shane P. Griffiths; Fabrice R. A. Jaine; Ian R. Tibbetts; Mike B. Bennett (Marine Biology, 2014)

The roles of oxygen and ammonia in the symbiotic relationship between the spotted salamander Ambystoma maculatum and the green alga Oophila amblystomatis during embryonic development - Daniel P. Small; R. Scott Bennett; Cory D. Bishop (Symbiosis, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Performance of an empirical bias‐correction of a high‐resolution climate dataset - James C. Bennett; Michael R. Grose; Stuart P. Corney; Christopher J. White; Gregory K. Holz; Jack J. Katzfey; David A. Post; Nathaniel L. Bindoff (International Journal of Climatology, 2014)
We describe the method and performance of a bias‐correction applied to high‐resolution (˜10 km) simulations from a stretched‐grid Regional Climate Model ( RCM ) over Tasmania, Australia. The bias‐correction is a quantile mapping of empirical cumulative frequency distributions. Corrections are applied at a daily time step to five variables: rainfall, potential evaporation (PE), solar radiation, maximum temperature and minimum temperature. Corrections are calculated independently for each season. We show that quantile mapping of empirical distributions can be highly effective in correcting biases in RCM outputs. Cross‐validation shows biases are effectively reduced across the range of cumulative frequency distributions, with few exceptions. The bias‐correction is not as effective at correcting biases for values at or near zero (e.g. in rainfall simulations), although even here the bias‐correction improves biases evident in the uncorrected simulations. In addition, the bias‐correction improves frequency characteristics of variables such as the number of rain days. We use a detrending technique to apply the bias‐correction to 140‐year time series of RCM variables. We show that the bias‐correction effectively preserves long‐term changes (e.g. to the mean and variance) to variables projected by the uncorrected RCM simulations. Correlations between key variables are also largely preserved, thus the bias‐corrected outputs reflect the dynamics of the underlying RCM . However, the bias‐corrected simulations still exhibit some of the deficiencies of the RCM simulations, e.g. the tendency to underestimate the magnitude and duration of large, multi‐day rain events, and the tendency to underestimate the duration of dry spells. The bias‐corrected simulations for six downscaled GCMs for the A2 and B1 emissions scenarios are available to researchers from http://www.tpac.org.au .

Aerobic fitness and cognitive function in midlife: an association mediated by plasma insulin - Takashi Tarumi; Mitzi M. Gonzales; Bennett Fallow; Nantinee Nualnim; Jeongseok Lee; Hirofumi Tanaka; Andreana P. Haley (Metabolic Brain Disease, 2013)

Seasonal changes in burrow geometry of the common mole rat (Rodentia: Bathyergidae) - H. G. Thomas; M. Scantlebury; D. Swanepoel; P. W. Bateman; N. C. Bennett (The Science of Nature, 2013)

Sex-biased dispersal in a rare butterfly and the implications for its conservation - Victoria J. Bennett; Shalynn M. Pack; Winston P. Smith; Matthew G. Betts (Journal of Insect Conservation, 2013)

A standardised protocol for the validation of banking methodologies for arterial allografts - R. J. Lomas; P. D. F. Dodd; P. Rooney; D. E. Pegg; P. A. Hogg; M. E. Eagle; K. E. Bennett; A. Clarkson; J. N. Kearney (Cell and Tissue Banking, 2013)

Comparative morphology of the egg cases of Asymbolus analis , Asymbolus rubiginosus and Figaro boardmani (Carcharhiniformes: Scyliorhinidae) from southern Queensland, Australia - C. Bustamante; P. M. Kyne; M. B. Bennett (Journal of Fish Biology, 2013)
Descriptions of the egg cases of three catsharks, Asymbolus analis , Asymbolus rubiginosus and Figaro boardmani , are provided from 65 egg cases obtained from fishing surveys carried out on the continental shelf of southern Queensland, Australia. Egg cases of A. analis , A. rubiginosus and F. boardmani have the same basic morphology; they are typically vase‐shaped, dorso‐ventrally flattened and yellow and brown‐tan in colour. The shape of the posterior border in terms of horn length and tendril thickness is the specific characteristic discriminating these three catsharks: enclosed horns in F. boardmani , short horns and tendrils in A . rubiginosus and long, coiled tendrils in A . analis . A non‐parametric statistical approach was used as an exploratory tool for egg case identification in which six proportional measurements were sufficient to discriminate between species. Three egg cases of F . boardmani were recovered from the stomachs of three A. rubiginosus , which provided the first evidence of catshark–catshark predator–prey interaction.

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

A regional response in mean westerly circulation and rainfall to projected climate warming over Tasmania, Australia - Michael R. Grose; Stuart P. Corney; Jack J. Katzfey; James C. Bennett; Gregory K. Holz; Christopher J. White; Nathaniel L. Bindoff (Climate Dynamics, 2013)

Complete genome sequence of arracacha virus B: a novel cheravirus - I. P. Adams; R. Glover; R. Souza-Richards; S. Bennett; U. Hany; N. Boonham (Archives of Virology, 2013)

Prenatal tobacco exposure predicts differential brain function during working memory in early adolescence: a preliminary investigation - David S. Bennett; Feroze B. Mohamed; Dennis P. Carmody; Muhammed Malik; Scott H. Faro; Michael Lewis (Brain Imaging and Behavior, 2013)

Aerobic Fitness and the Brain: Increased N-Acetyl-Aspartate and Choline Concentrations in Endurance-Trained Middle-Aged Adults - Mitzi M. Gonzales; Takashi Tarumi; Sonya Kaur; Nantinee Nualnim; Bennett A. Fallow; Martha Pyron; Hirofumi Tanaka; Andreana P. Haley (Brain Topography, 2013)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Feeding ecology and dietary comparisons among three sympatric Neotrygon (Myliobatoidei: Dasyatidae) species - I. P. Jacobsen; M. B. Bennett (Journal of Fish Biology, 2012)
The diets of Neotrygon picta , Neotrygon kuhlii and Neotrygon annotata are described using trophic level analysis, index of relative importance ( I RI ) and non‐metric multidimensional scaling ordination (nMDS). They were secondary consumers with trophic levels of between 3·55 and 3·58. Carids were the most important prey category in the diets of N. picta (82·0% I RI ) and N. annotata (69·4% I RI ); Polychaeta (72·3% I RI ) was the most important prey category for N. kuhlii . A significant difference was detected between the volumetric dietary data of all three species (ANOSIM, global R ‐statistic = 0·742, P N. picta and N. kuhlii size classes (ANOSIM, global R ‐statistics = 0·367–0·403, P Neotrygon species, and the potential for resource partitioning to occur when these species coexist.

Waves and weathering at 3.7 Ga: Geological evidence for an equitable terrestrial climate under the faint early Sun - A. P. Nutman; V. C. Bennett; C. R. L. Friend (Australian Journal of Earth Sciences, 2012)

Developing X-ray Computed Tomography to non-invasively image 3-D root systems architecture in soil - S. J. Mooney; T. P. Pridmore; J. Helliwell; M. J. Bennett (Plant and Soil, 2012)

Evidence for Mate Guarding Behavior in the Taylor’s Checkerspot Butterfly - Victoria J. Bennett; Winston P. Smith; Matthew G. Betts (Journal of Insect Behavior, 2012)

Associations of whole-blood fatty acids and dietary intakes with prostate cancer in Jamaica - Maria D. Jackson; Susan P. Walker; Candace M. Simpson-Smith; Carole M. Lindsay; Garret Smith; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2012)

Structure, Function, and Mechanism of Progranulin; the Brain and Beyond - Huishi Toh; Babykumari P. Chitramuthu; Hugh P. J. Bennett; Andrew Bateman (Journal of Molecular Neuroscience, 2011)

To know or not to know: influence of explicit advance knowledge of occlusion on interceptive actions - Pieter Tijtgat; Simon J. Bennett; Geert J. P. Savelsbergh; Dirk De Clercq; Matthieu Lenoir (Experimental Brain Research, 2011)

The effectiveness of methicillin-resistant Staphylococcus aureus colonisation screening in asymptomatic healthcare workers in an Irish orthopaedic unit - S. P. Edmundson; K. M. Hirpara; D. Bennett (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

The relative timing between eye and hand in rapid sequential pointing is affected by time pressure, but not by advance knowledge - F. J. A. Deconinck; V. van Polanen; G. J. P. Savelsbergh; S. J. Bennett (Experimental Brain Research, 2011)

Archaean fluid-assisted crustal cannibalism recorded by low δ18O and negative εHf(T) isotopic signatures of West Greenland granite zircon - Joe Hiess; Vickie C. Bennett; Allen P. Nutman; Ian S. Williams (Contributions to Mineralogy and Petrology, 2011)

Low levels of polymorphism at novel microsatellite loci developed for bathyergid mole-rats from South Africa - T. C. Bray; N. C. Bennett; P. Bloomer (Conservation Genetics Resources, 2011)

Micronutrient Mineral and Folate Content of Australian and Imported Dried Fruit Products - Louise E. Bennett; Davinder P. Singh; Peter R. Clingeleffer (Critical Reviews in Food Science and Nutrition, 2010)

Urinary phytoestrogens and risk of prostate cancer in Jamaican men - Maria D. Jackson; Norma D. McFarlane-Anderson; Garfield A. Simon; Franklyn I. Bennett; Susan P. Walker (Cancer Causes & Control, 2010)

Age and growth of Neotrygon picta, Neotrygon annotata and Neotrygon kuhlii from north‐east Australia, with notes on their reproductive biology - I. P. Jacobsen; M. B. Bennett (Journal of Fish Biology, 2010)
Vertebral band formations were used to define age and growth in three Neotrygon species caught regularly as by‐catch in prawn trawl fisheries in north‐east Australia. Centrum edge and marginal increment ratio analyses were used to validate annual band formations. Age estimates ranged from 1 to 18 years, with the von Bertalanffy growth function considered to have the best fit to Neotrygon picta (males, W D∞ = 271 mm, k = 0·12; females, W D∞ = 360·5 mm, k = 0·08) and Neotrygon kuhlii (males, W D∞ = 438·6 mm, k = 0·08; females, W D∞ = 440·6 mm, k = 0·08) disc width ( W D )‐at‐age data. The Gompertz growth function had the best fit to Neotrygon annotata W D ‐at‐age data (males, W D∞ = 230·4 mm, k = 0·20; females, W D∞ = 265·5 mm, k = 0·31). Age at sexual maturity ranged from 3 to 6 years, with N. picta having the smallest size at birth (100 mm W D ), smallest W D at 50% maturity ( W D50 : male, 172 mm, female, 180·7 mm) and lowest age at sexual maturity (3–4 years). This study helps redefine and improve the accuracy of fisheries‐based risk assessments for these small species with relatively conservative life‐history variables.

“I have always believed I was at high risk…” The role of expectation in emotional responses to the receipt of an average, moderate or high cancer genetic risk assessment result: a thematic analysis of free-text questionnaire comments - J. Hilgart; C. Phelps; P. Bennett; K. Hood; K. Brain; A. Murray (Familial Cancer, 2010)

Broad‐scale environmental response and niche conservatism in lacustrine diatom communities - Joseph R. Bennett; Brian F. Cumming; Brian K. Ginn; John P. Smol (Global Ecology and Biogeography, 2010)
Aim (1) To resolve theoretical debates regarding the role of environment versus dispersal limitation, the conservatism of niches across distances and the prevalence of environmental specialists in diatom communities. (2) To provide guidance on the use of diatom communities and other microbial analogues to analyse ecological response to environmental change. Location Eight hundred and ninety‐one lakes in five regional datasets from north‐western Europe and four regional datasets from north‐eastern North America. Methods Lacustrine diatom communities were analysed at three scales: inter‐continental, intra‐continental and regional. Nested partial redundancy analyses (RDAs) were used to determine spatial versus environmental components of community variation. Weighted‐averaging (WA) regression and calibration, as well as logistic and quadratic regressions, were used to detect niche conservatism and the prevalence of environmental specialists. Results Community patterns indicate that dispersal limitation acts predominantly at the inter‐continental scale, while at the regional (less than c . 1,000,000 km 2 ) scale, a single environmental variable (pH) explains more than five times the community variation as spatial (dispersal‐related) variables. In addition, pH niche components appear to be conserved at the inter‐continental scale, and environmental specialization does not impose relative rarity, as specialists apparently readily disperse to suitable environments. Main conclusions Analysis at multiple scales is clearly important in determining the influences of community variation. For diatom communities, dispersal limitation acts most strongly at the broadest scales, giving way to environment at the scales considered by most analyses. The availability of a wide variety of propagules with consistent niches across regions indicates that diatom communities reflect the succession of taxa according to local environmental conditions, rather than disequilibrium with the environment or adaptation of local populations. While multi‐scale analyses must be undertaken for other groups to resolve debates over community drivers and determine appropriate scales for prediction, for diatoms (and probably other microbial communities), responses to environmental change can be inferred using analogue datasets from large geographic areas.

Body size and risk of prostate cancer in Jamaican men - Maria D. Jackson; Susan P. Walker; Candace M. Simpson; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2010)

Rescue of Drosophila Melanogaster l(2)35Aa lethality is only mediated by polypeptide GalNAc-transferase pgant35A, but not by the evolutionary conserved human ortholog GalNAc-transferase-T11 - Eric P. Bennett; Ya-Wen Chen; Tilo Schwientek; Ulla Mandel; Katrine ter-Borch Gram Schjoldager; Stephen M. Cohen; Henrik Clausen (Glycoconjugate Journal, 2010)

Advance knowledge effects on kinematics of one-handed catching - Pieter Tijtgat; Simon J. Bennett; Geert J. P. Savelsbergh; Dirk De Clercq; Matthieu Lenoir (Experimental Brain Research, 2010)

Diet and reproduction in the Australian butterfly ray Gymnura australis from northern and north‐eastern Australia - I. P. Jacobsen; J. W. Johnson; M. B. Bennett (Journal of Fish Biology, 2009)
The diet of Gymnura australis was dominated by teleosts (99·8% index of relative importance). A wide‐ranging species, females matured at 446 mm disc width ( W D ), had a single functional ovary and two functional uteri. Males matured at 377 mm W D and had a single functional testis.

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)

Global biogeography and ecology of body size in birds - Valérie A. Olson; Richard G. Davies; C. David L. Orme; Gavin H. Thomas; Shai Meiri; Tim M. Blackburn; Kevin J. Gaston; Ian P. F. Owens; Peter M. Bennett (Ecology Letters, 2009)
In 1847, Karl Bergmann proposed that temperature gradients are the key to understanding geographic variation in the body sizes of warm‐blooded animals. Yet both the geographic patterns of body‐size variation and their underlying mechanisms remain controversial. Here, we conduct the first assemblage‐level global examination of ‘Bergmann’s rule’ within an entire animal class. We generate global maps of avian body size and demonstrate a general pattern of larger body sizes at high latitudes, conforming to Bergmann’s rule. We also show, however, that median body size within assemblages is systematically large on islands and small in species‐rich areas. Similarly, while spatial models show that temperature is the single strongest environmental correlate of body size, there are secondary correlations with resource availability and a strong pattern of decreasing body size with increasing species richness. Finally, our results suggest that geographic patterns of body size are caused both by adaptation within lineages, as invoked by Bergmann, and by taxonomic turnover among lineages. Taken together, these results indicate that while Bergmann’s prediction based on physiological scaling is remarkably accurate, it is far from the full picture. Global patterns of body size in avian assemblages are driven by interactions between the physiological demands of the environment, resource availability, species richness and taxonomic turnover among lineages.

The dapE-encoded N-succinyl-l,l-diaminopimelic acid desuccinylase from Haemophilus influenzae contains two active-site histidine residues - Danuta M. Gillner; David L. Bienvenue; Boguslaw P. Nocek; Andrzej Joachimiak; Vincentos Zachary; Brian Bennett; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2009)

Regional variation in the historical components of global avian species richness - Gavin H. Thomas; C. David L. Orme; Richard G. Davies; Valerie A. Olson; Peter M. Bennett; Kevin J. Gaston; Ian P. F. Owens; Tim M. Blackburn (Global Ecology and Biogeography, 2008)
Aim Using a global data base of the distribution of extant bird species, we examine the evidence for spatial variation in the evolutionary origins of contemporary avian diversity. In particular, we assess the possible role of the timing of mountain uplift in promoting diversification in different regions. Location Global. Methods We mapped the distribution of avian richness at four taxonomic levels on an equal‐area 1° grid. We examined the relationships between richness at successive taxonomic levels (e.g. species richness vs. genus richness). We mapped the residuals from linear regressions of these relationships to identify areas that are exceptional in the number of lower taxa relative to the number of higher taxa. We use generalized least squares models to test the influence of elevation range and temperature on lower‐taxon richness relative to higher‐taxon richness. Results Peaks of species richness in the Neotropics were congruent with patterns of generic richness, whilst peaks in Australia and the Himalayas were congruent with patterns of both genus and family richness. Hotspots in the Afrotropics did not reflect higher‐taxon patterns. Regional differences in the relationship between richness at successive taxonomic levels revealed variation in patterns of taxon co‐occurrence. Species and genus co‐occurrence was positively associated with elevational range across much of the world. Taxon occurrence in the Neotropics was associated with a positive interaction between elevational range and temperature. Conclusions These results demonstrate that contemporary patterns of richness show different associations with higher‐taxon richness in different regions, which implies that the timing of historical effects on these contemporary patterns varies across regions. We suggest that this is due to dispersal limitation and phylogenetic constraints on physiological tolerance limits promoting diversification. We speculate that diversification rates respond to long‐term changes in the Earth's topography, and that the role of tropical mountain ranges is implicated as a correlate of contemporary diversity, and a source of diversification across avian evolutionary history.

Comparing the diet of two sympatric urolophid elasmobranchs ( Trygonoptera testacea Müller & Henle and Urolophus kapalensis Yearsley & Last): evidence of ontogenetic shifts and possible resource partitioning - A. D. Marshall; P. M. Kyne; M. B. Bennett (Journal of Fish Biology, 2008)
The diets of two urolophids, the common stingaree Trygonoptera testacea and the kapala stingaree Urolophus kapalensis were analysed and compared to examine resource partitioning between these two morphologically similar sympatric Australian batoids. The diet of T. testacea was polychaete‐based, while that of U. kapalensis was dominated by crustaceans (mostly carid shrimps and amphipods). Intraspecific dietary compositions were examined amongst size classes within each of the two species to identify ontogenetic shifts in diet. Differences in the dietary compositions of the smaller total‐length classes of T. testacea suggest that their diet shifts as they increase in size, from one dominated by carids to one almost entirely comprising polychaetes. Significant ontogenetic dietary shifts were not identified in U. kapalensis . Although the two species shared eight broad dietary categories, their overall dietary compositions were found to be significantly different. The limited overlap in the dietary compositions of these two sympatric stingarees suggests the possibility of resource partitioning, with interspecific competition being implicated as a possible cue. Possible mechanisms for the partitioning of resources within and between these two species are discussed.

Seawater-like trace element signatures (REE + Y) of Eoarchaean chemical sedimentary rocks from southern West Greenland, and their corruption during high-grade metamorphism - C. R. L. Friend; A. P. Nutman; V. C. Bennett; M. D. Norman (Contributions to Mineralogy and Petrology, 2008)

Aspects of reproduction and diet of the Australian endemic skate Dipturus polyommata (Ogilby) (Elasmobranchii: Rajidae), by‐catch of a commercial prawn trawl fishery - P. M. Kyne; A. J. Courtney; M. B. Bennett (Journal of Fish Biology, 2008)
The Australian endemic skate Dipturus polyommata collected from by‐catch of a benthic prawn fishery off southern Queensland was examined to provide information on reproduction and diet. Morphological relationships of total length ( L T ) to disc width and L T to mass were estimated. Size at birth was estimated at c. 100–110 mm and size at first feeding at c. 105–110 mm L T . Size at 50% maturity ( L T50 and 95% CI) was 321 (305–332) and 300 (285–306) mm L T for females and males, respectively. Size at first maturity corresponded to 87·7% of observed maximum size in females (366 mm L T ) and 87·5% in males (343 mm L T ). Two females, representing 18·2% of mature females sampled in the austral winter were each carrying two egg cases. Descriptions of egg cases are given. Diet described by the index of relative importance as a percentage (% I RI ) was predominantly crustacean based with carid shrimps (53·64%) and penaeoid prawns (23·30%) the most significant prey groups. Teleosts (11·72%), gammarid amphipods (5·31%) and mysids (4·72%) were also important to the diet of the species, while a further six prey groups made only a minor contribution to diet (1·31%). An ontogenetic change was evident between the diets of immature and mature skates. Immature animals fed more extensively on carids and amphipods and mature animals on penaeoids, teleosts and mysids.

∼3,850 Ma tonalites in the Nuuk region, Greenland: geochemistry and their reworking within an Eoarchaean gneiss complex - Allen P. Nutman; Vickie C. Bennett; Clark R. L. Friend; Kenji Horie; Hiroshi Hidaka (Contributions to Mineralogy and Petrology, 2007)

Continuous measurement of oxygen tensions in the air-breathing organ of Pacific tarpon (Megalops cyprinoides) in relation to aquatic hypoxia and exercise - Roger S. Seymour; Anthony P. Farrell; Keith Christian; Timothy D. Clark; Michael B. Bennett; Rufus M. G. Wells; John Baldwin (Journal of Comparative Physiology B, 2007)

Size matters: genital allometry in an African mole-rat (Family: Bathyergidae) - A. A. Kinahan; N. C. Bennett; M. J. O’Riain; L. Hart; P. W. Bateman (Evolutionary Ecology, 2007)

Energy, range dynamics and global species richness patterns: reconciling mid‐domain effects and environmental determinants of avian diversity - David Storch; Richard G. Davies; Samuel Zajíček; C. David L. Orme; Valerie Olson; Gavin H. Thomas; Tzung‐Su Ding; Pamela C. Rasmussen; Robert S. Ridgely; Peter M. Bennett; Tim M. Blackburn; Ian P. F. Owens; et al. (Ecology Letters, 2006)
Spatial patterns of species richness follow climatic and environmental variation, but could reflect random dynamics of species ranges (the mid‐domain effect, MDE). Using data on the global distribution of birds, we compared predictions based on energy availability (actual evapotranspiration, AET, the best single correlate of avian richness) with those of range dynamics models. MDE operating within the global terrestrial area provides a poor prediction of richness variation, but if it operates separately within traditional biogeographic realms, it explains more global variation in richness than AET. The best predictions, however, are given by a model of global range dynamics modulated by AET, such that the probability of a range spreading into an area is proportional to its AET. This model also accurately predicts the latitudinal variation in species richness and variation of species richness both within and between realms, thus representing a compelling mechanism for the major trends in global biodiversity.

Complex evolution of X and Y autosomal translocations in the giant mole-rat, Cryptomys mechowi (Bathyergidae) - J. L. Deuve; N. C. Bennett; P. C. M. O’Brien; M. A. Ferguson-Smith; C. G. Faulkes; J. Britton-Davidian; T. J. Robinson (Chromosome Research, 2006)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

A New Interpretation of Avian and Mammalian Reproduction Toxicity Test Data in Ecological Risk Assessment - Richard S. Bennett; I.C. Dewhurst; A. Fairbrother; A.D.M. Hart; M.J. Hooper; A. Leopold; P. Mineau; S.R. Mortensen; R.F. Shore; T.A. Springer (Ecotoxicology, 2005)

Identification of flanking SSR markers for a major rice gall midge resistance gene Gm1 and their validation - S. K. Biradar; R. M. Sundaram; T. Thirumurugan; J. S. Bentur; S. Amudhan; V. V. Shenoy; B. Mishra; J. Bennett; N. P. Sarma (Theoretical and Applied Genetics, 2004)

Coordinating degrees of freedom during interceptive actions in children - Annieck X. C. Ricken; Geert J. P. Savelsbergh; Simon J. Bennett (Experimental Brain Research, 2004)

Criteria to Assess and Select Sites for Long-Term Avian Monitoring in an Urbanizing Landscape - Lorne P. Bennett; Robert J. Milne (Environmental Monitoring and Assessment, 2004)

Neonatal small bowel epithelia: enhancing anti-bacterial defense with lactoferrin and Lactobacillus GG - Michael P. Sherman; Stephen H. Bennett; Freda F.Y. Hwang; Camille Yu (BioMetals, 2004)

Cloning and Characterization of the NAD-Dependent 7?-Hydroxysteroid Dehydrogenase from Bacteroides fragilis - Michael J. Bennett; Susan L. McKnight; James P. Coleman (Current Microbiology, 2003)

Variants of the CD40 ligand gene are not associated with increased susceptibility to tuberculosis in West Africa - Sarah J. Campbell; Pardis Sabeti; Katherine Fielding; Jackson Sillah; Boubacar Bah; Per Gustafson; Kebba Manneh; Ida Lisse; Giorgio Sirugo; Richard Bellamy; Steve Bennett; Peter Aaby; et al. (Immunogenetics, 2003)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Human infection by a swine influenza A (H1N1) virus in Switzerland - V. Gregory; M. Bennett; Y. Thomas; L. Kaiser; W. Wunderli; H. Matter; A. Hay; Y. P. Lin (Archives of Virology, 2003)

[3H]-thymidine labelling of DNA triggers apoptosis potentiated by E1A-adenoviral protein - S. N. Orlov; D. V. Pchejetski; S. Der Sarkissian; V. Adarichev; S. Taurin; A. V. Pshezhetsky; J. Tremblay; G. V. Maximov; D. deBlois; M. R. Bennett; P. Hamet (Apoptosis, 2003)

Association of bovine neonatal Fc receptor a-chain gene (FCGRT) haplotypes with serum IgG concentration in newborn calves - William W. Laegreid; Michael P. Heaton; James E. Keen; William M. Grosse; Carol G. Chitko-McKown; Timothy P.L. Smith; John W. Keele; Gary L. Bennett; Thomas E. Besser (Mammalian Genome, 2002)

Selection and use of SNP markers for animal identification and paternity analysis in U.S. beef cattle - Michael P. Heaton; Gregory P. Harhay; Gary L. Bennett; Roger T. Stone; W. Michael Grosse; Eduardo Casas; John W. Keele; Timothy P.L. Smith; Carol G. Chitko-McKown; William W. Laegreid (Mammalian Genome, 2002)

Reproductive suppression and inbreeding avoidance in wild populations of co-operatively breeding meerkats ( Suricata suricatta ) - M. J. O'Riain; N. C. Bennett; P. N. M. Brotherton; G. McIlrath; T. H. Clutton-Brock (Behavioral Ecology and Sociobiology, 2000)

Discriminating the role of binocular information in the timing of a one-handed catch - Simon J. Bennett; John van der Kamp; Geert J. P. Savelsbergh; Keith Davids (Experimental Brain Research, 2000)

Non-erythroid form of acute intermittent porphyria caused by promoter and frameshift mutations distant from the coding sequence of exon 1 of the HMBS gene - Sharon D. Whatley; Andrew G. Roberts; David H. Llewellyn; Christopher P. Bennett; Christine Garrett; George H. Elder (Human Genetics, 2000)

Comparative map alignment of BTA27 and HSA4 and 8 to identify conserved segments of genome containing fat deposition QTL - Tad S. Sonstegard; Wes M. Garrett; Melissa S. Ashwell; Gary L. Bennett; Steven M. Kappes; Curtis P. Van Tassell (Mammalian Genome, 2000)

Molecular cloning of transmembrane and soluble forms of a novel rat natural killer cell receptor related to 2B4 - P. R. Kumaresan; S. E. Stepp; M. Bennett; V. Kumar; P. A. Mathew (Immunogenetics, 2000)

Meta-igneous (non-gneissic) tonalites and quartz-diorites from an extensive ca. 3800 Ma terrain south of the Isua supracrustal belt, southern West Greenland: constraints on early crust formation - Allen P. Nutman; Vickie C. Bennett; Clark R. L. Friend; Marc D. Norman (Contributions to Mineralogy and Petrology, 1999)

Interactive effects of subanesthetic ketamine and haloperidol in healthy humans - John H. Krystal; D. Cyril D'Souza; Laurence P. Karper; Alexandre Bennett; Anissa Abi-Dargham; Danielle Abi-Saab; Karyn Cassello; M. B. Bowers Jr.; Sally Vegso; George R. Heninger; Dennis S. Charney; M. B. Bowers (Psychopharmacology, 1999)

Alternative transcription initiation sites generate two LCA1 Ca2+-ATPase mRNA transcripts in tomato roots - Juan P. Navarro-Avino; Audrey E. Hentzen; Alan B. Bennett (Plant Molecular Biology, 1999)

High-resolution paleoecological analysis of recent disturbance in a southern Chilean Nothofagus forest - Julian M. Szeicz; Barbara A. Zeeb; K.D. Bennett; John P. Smol (Journal of Paleolimnology, 1998)

Novel Chitinolytic Enzymes with Biological Activity Against Herbivorous Insects - Roxanne M. Broadway; Carmenza Gongora; Wendy C. Kain; John P. Sanderson; Jose A. Monroy; K. C. Bennett; Jason B. Warner; Michael P. Hoffmann (Journal of Chemical Ecology, 1998)

Mercury Accumulation in Transplanted Hypogymnia Physodes Lichens Downwind of Wisconsin Chlor-Alkali Plant - M. M. Makholm; J. P. Bennett (Water, Air, & Soil Pollution, 1998)

Interactive effects of subanesthetic ketamine and subhypnotic lorazepam in humans - John H. Krystal; Laurence P. Karper; Alexandre Bennett; D. Cyril D'Souza; Anissa Abi-Dargham; Kristen Morrissey; Danielle Abi-Saab; J. Douglas Bremner; M. B. Bowers Jr.; Raymond F. Suckow; Philip Stetson; George R. Heninger; et al. (Psychopharmacology, 1998)

The Cystatin S gene maps to rat Chromosome 3, to which Dlmgh18 is re-assigned from Chromosome 1 - M. Beatriz Duran Alonso; Paul Shiels; Andrew S. McCallion; Neil K. Bennett; Anthony P. Payne; Josiane Szpirer; Claude Szpirer; Martin J. Brodie; R. Wayne Davies; Roger G. Sutciffe (Mammalian Genome, 1997)

Announcement - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Erratum - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Loss of cell surface microvilli on rat basophilic leukaemia cells precedes secretion and can be mimicked using the calmodulin antagonist trifluoperazine - A. J. Edgar; G. R. Davies; M. A. Anwar; J. P. Bennett (Inflammation Research, 1997)

Zipping up transcription factors: Rational design of anti-Jun and anti-Fos peptides - Naresh P. S. Bains; Jackie A. Wilce; Katja H. Heuer; Mark Tunstall; Joel P. Mackey; Max R. Bennett; Anthony S. Weiss; Glenn F. King (International Journal of Peptide Research and Therapeutics, 1997)

Multiplicity of uses of monoclonal antibodies that define papillomavirus linear immunodominant epitopes - A. Bennett Jenson; Michelle C. Jenson; Lex Cowsert; Shin-je Ghim; John P. Sundberg (Immunologic Research, 1997)

Polymerase chain reaction for detection of herpesvirus simiae (B virus) in clinical specimens - M. J. Slomka; D. W. G. Brown; J. P. Clewley; A. M. Bennett; L. Harrington; D. C. Kelly (Archives of Virology, 1993)

Identification and sequence determination of the capsid protein gene of feline calicivirus - M. J. Carter; I. D. Milton; P. C. Turner; J. Meanger; M. Bennett; R. M. Gaskell (Archives of Virology, 1992)

Fatty acid composition ofAerobacter aerogenes - C. P. Truby; E. O. Bennett (Antonie van Leeuwenhoek, 1971)

Biological control ofDiatraea saccharalis (F.) in Barbados byApanteles flavipes Cam. andLixophaga Diatraeae T. T. - M. M. Alam; F. D. Bennett; K. P. Carl (BioControl, 1971)

Sectional notes - C. H. Metzger; E. R. Bennett; W. B. Ward; J. G. Richard; Ralph W. Donaldson; T. M. Patterson; L. Harris; Marx Koehnke; J. M. Jenkins; W. H. Martin; Robert Schmidt; E. M. Gillig; et al. (American Journal of Potato Research, 1937)

Preliminary seed potato certification notes - C. Tice; E. P. Sandsten; E. R. Bennett; F. M. Harrington; H. O. Werner; J. A. Hill (American Journal of Potato Research, 1923)